General characteristics of rare earth and radioactive elements in Dong Pao deposit, Lai Chau, Vietnam - Chau*, Nguyen Dinh; Jadwiga, Pieczonka; Adam, Piestrzyński; Hao, Duong Van; Phon, Le Khanh; Paweł, Jodłowski (Vietnam Journal of Earth Sciences, 2017)
One of the important rare earth deposits is the Dong Pao localized in Lai Chau province, West-North of Vietnam. Generally, the deposit is composed of two parts, the lower and the upper. The lower part is composed of dolomite, limestone and intrusive rocks, while the upper part of the profile is represented by a weathered zone containing soil and fragments of mixed barite-fluorite ores. The concentrations of natural radionuclides, chemical compositions of ores, including rare earth elements (REE) in solid samples, were determined by gamma spectrometer equipped with a HPGe detector, laser ablation inductively coupled plasma mass spectrometry (LA ICPMS) and activation method, respectively. In the samples taken from the ore bodies within the weathered zone the REE concentration is about 10 wt.% and both 238U and 232Th amount to 0.01 wt.%, while in the samples from the hard part of ore the REE and 238U as well as 232Th contents amount only to 0.3 wt.% and 0.001 wt.%, respectively. So the enrichment of the REE and natural radioactive elements in the deposit is a consequence of the weathering processes. The water samples were taken from the streams, natural tap and thermal water intakes localized in the studied deposit and surrounding region. The 238U, 234U, 228Ra, 226Ra concentrations in the water samples were prepared by the adequate radiochemical procedures and measured using an alpha spectrometer coupled with silicon semiconductor detector and a/b liquid scintillation counter. In the stream water, the concentrations of both 226Ra and 228Ra vary from 100 to above 300 mBq/L, while in the natural tap and thermal waters they amount to tens mBq/L. The concentration of 238U, 234U in the thermal water is 80 and 110 mBq/L respectively, while in the surface water concentrations of uranium isotopes are below 30 mBq/L. References Bureau Veritas Canada, 2015. Certificate of analysis No KRA 15000229.1 Curtis N., 2011. Lynas Report. https://www.lynascorp.com/Pages/Reporting-centre-Annual-report.aspx. Damascena K.R., et al., 2015. Rare-earth elements in uranium deposits in the municipaliity of Pedra, Pernambuco, Brazil. J. Radioanal. Nucl. Chem. 304, 1053-1058. Dovzikov A.E., 1965. Geology of North Vietnam, explanation and interpretation for the Geological Map of North Vietnam. Vietnam Geol. Depart. (in Russian). Faure, M., Lepvrier, C., Van Nguyen, V., Van Vu, T., Lin, W., & Chen, Z., 2014. The South China Block-Indochina collision: where, when, and how? Journal of Asian Earth Sciences, 79, 260-274. Fromaget J., 1941. Geological structure, deposits related to tectonics of Indochina. Indochina Geol. Biul. XXVI(2), (in France). Fromaget J., Saurin E., 1952. Geological map of Indochina 1:200.000. National Geograph Institute of France. Halpin J.A., Tran T.H., Lai C.K., Meffre S., Crawford A.J., Zaw K., 2015. U-Pb zircon geochronology and geochemistry from NE Vietnam: A “tectonically disputed” territory between the Indochina and South China blocks. Gondwana Research, http://dx.doi.org/10.1016/j.gr.2015.04.005. Hoatson D.M., Jaireth S., Miezitis Y., 2011. The major Rare-Earth element deposits of Australia: Geological setting, exploration and resources. Australian Government, Geoscience Australia, 193. Hornig-Kjarsgaard I., 1998. Rare earth elements in sovitic carbonatites and their mineral phases. J. Petrology, 39, 2105-2121. Hou B., 2005. Heavy mineral sands potential of the Eucla Basin in South Australia - a world-class palaeobeach placer province. MESA Journal, 37, 4-12. Jodłowski P., Kalita S., 2010. Gamma-Ray Spectrometry Laboratory for high-precision measurements of radionuclide concentrations in environmental samples. Nukleonika, 55(2), 143-148. Kušnir I., 2000. Mineral resources of Vietnam. Acta Montanista Slovaca, 5(2), 165-172. Le Khanh Phon, Bui Dac Dung, Nguyen Dinh Chau, Tibor Kovacs, Nguyen Van Nam, Dong Van Hao, Nguyen Tai Son, Vu Thi Minh Luan, 2015. Estimation of effective dose ratek caused by radon and toron for inhabitants living in rare earth field in north Wietnam (Lai Chau province). J. Radioanal. Nucl. Chem, 306, 309-316. Liu Y., Hu Z., Gao S., Günther D., Xu J., Gao C., Chen H., 2008. In situ analysis of major and trace elements of anhydrous minerals by LA-ICP-MS without applying an internal standard. Chem. Geol. 257, 34-43. Nguyen Dinh Chau, Niewodniczański J., Dorda J., Ochoński A., Chruściel E., Tomza I., 1997. Determination of radium isotopes in mine waters through alpha- and beta-activities measured by liquid scintillation spectrometry. J. Radioanal. Nucl. Chem., 222(1-2), 69-74. Nguyen Dinh Chau, Le K.P., Jodłowski P., Pieczonka J., Piestrzyński A., Duong V.H., Nowak J., 2016. Natural Radioactivity at the Sin Quyen Iron-Oxide-Copper-Gold Deposit in North Vietnam. Acta Geophys, 64(6), 2305-2321. Nguyen Tien Du, et al., 2011. Report of the supplementary geological prospecting surveys at the Rare Earth Elements at Dong Pao Deposit, Ban Giang District, Lai Chau province, Nort-Weast Vietnam. Archive at the Geological Division VIMICO, Lai Chau. (in Vietnames), 215. Pham Ngoc Can, Ishiyama D., Tran Tuan Anh, Sera K., 2011. Mineralogical and geochemical characteristics of rare metals-bearing Na Bop, Lung Hoai, Na Son and Sin Quyen base metal deposits, North Vietnam. NMCC Annual Report 18, 49-55. Rösler H.J, Lange H., 1976. Geochemical Tables, Edition Leipzig, 468. Tran Van Tri 2011. Geology and Earth Resources of Vietnam [in] Vu Khuc (ed). General Dept. of Geology and Minerals of Vietnam, Hanoi, Publishing House for Science and Technology, 634. Tran Trong Hoa, Tran Tuan Anh, Pham Thi Dung, Tran Quoc Hung, Bui An Nien, Tran Van Hieu, Pham Ngoc Can, 2010. Useful elements accompanying with the Pb-Zn and Cu deposits in the North Vietnam. Vietnam Journal of Earth Sciences, 32(4), 289-298. (in Vietnamese). WHO 2006. Guidelines for Drinking-water Quality, First Addendum to Third Edition, V Recommendations. New Jork, 595. Żelaźniewicz A., Tran T.H., Larionov A.N., 2013. The significance of geological and zircon age data derived from the wall rocks of the Ailao Shan-Red River shear zone, NW Vietnam. J. Geodynamics, 69, 122-139.